Theoretical insights on the luminescent mechanism of a highly efficient green-activated delayed fluorescence emitter using the QM/MM method. (17th January 2023) - Sun, Hai-Yang; Yu, Zi-Yue; Zhou, Ai-Ping; Wei, Shu-Li; Chang, Qiang; Zhang, Tian; Sun, Yu-Ping
Abstract : The solid-state effect plays an important role in excited-state dynamics and luminescence properties of thermally activated delayed fluorescence (TADF) materials. Here, the luminescent mechanism of two novel TADF emitters, PPZTPI and PPZPPI, with aggregation-induced emission (AIE) features are theoretically studied based on the first-principles calculations. The polarisable continuum model (PCM) and the combined quantum mechanics and molecular mechanics (QM/MM) method are used to simulate the solvent environments in toluene and the solid-state effects, respectively. Our results show that both PPZTPI and PPZPPI exhibit excellent TADF and AIE properties with similar but not identical luminescence mechanisms. In the solid state, the delayed fluorescence emission of the two molecules mainly depends on the two-step reverse intersystem crossing process. The molecular radiation rates increase by 1–2 orders of magnitude due to the enhancement of intermolecular interactions in the aggregation. For PPZTPI, the solid-state environment exerts a greater influence on the molecular geometry and electronic structure, non-radiative transitions, excited state dynamics, and emission mechanism due to the substitution of tert-butyl groups and their induced steric hindrance effects. Our theoretical study reasonably elucidates the experimental results and provides valuable information for designing high-efficient AIE-TADF emitters. GRAPHICAL ABSTRACT: UF0001